2021
DOI: 10.1002/jcp.30366
|View full text |Cite
|
Sign up to set email alerts
|

Role of pyroptosis in atherosclerosis and its therapeutic implications

Abstract: Atherosclerosis is a significant cardiovascular burden and a leading cause of death worldwide, recognized as a chronic sterile inflammatory disease. Pyroptosis is a novel proinflammatory regulated cell death, characterized by cell swelling, plasma membrane bubbling, and robust release of proinflammatory cytokines (such as interleukin IL‐1β and IL‐18). Mounting studies have addressed the crucial contribution of pyroptosis to atherosclerosis and clarified the candidate therapeutic agents targeting pyroptosis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 164 publications
0
32
0
Order By: Relevance
“…According to recent research, pyroptosis has an impact on the entire course of atherosclerosis [ 47 ]. Therefore, appropriate intervention in the activation of pyroptosis in atherosclerotic plaques may provide a new therapeutic strategy for patients with AS [ 48 ]. To predict effective therapeutic agents for atherosclerotic plaques, the DGIdb was used to identify drugs and molecular compounds that affect upregulated hub genes in the two pyroptosis-related clusters.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research, pyroptosis has an impact on the entire course of atherosclerosis [ 47 ]. Therefore, appropriate intervention in the activation of pyroptosis in atherosclerotic plaques may provide a new therapeutic strategy for patients with AS [ 48 ]. To predict effective therapeutic agents for atherosclerotic plaques, the DGIdb was used to identify drugs and molecular compounds that affect upregulated hub genes in the two pyroptosis-related clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of atherosclerosis involves smooth muscle cell proliferation and migration, endothelial cell dysfunction, pro-inflammatory cytokine secretion, and cell death 56 . Previous studies have illustrated that pyroptosis in macrophages, endothelial cells, and smooth muscle cells are related to the progression of atherosclerosis 57 . Duewell et al showed that cholesterol crystals can activate caspase-1 through the NLRP3 inflammasome, which cleaves pro-IL-18 and pro-IL-1β to produce their mature forms, resulting in inflammation and atherosclerosis formation 58 .…”
Section: Inhibiting Pyroptosis To Treat Inflammatory Diseasesmentioning
confidence: 99%
“…Morphologically, it is most likely to be a combination of apoptosis and necrosis. The pathogenesis of atherosclerosis is characterized by recruitment of monocytes and lymphocytes, dysfunction of ECs, formation of foam cells (FCs), proliferation of smooth muscle cells (SMCs), secretion of proinflammatory cytokines, accumulation and oxidation of LDL, adherence of platelets, and death of abundant cells [7] [81]. Previous studies have confirmed that atherosclerosis is mainly attributed to inflammation and the products of pyroptosis such as IL-1β, IL-18, IL-1α, ATP, and GSDMD-N, suggesting crucial role of pyroptosis in the pathogenesis of atheroscle-rosis [21][82] [83].…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%